Efektivitas Metode Diskusi Dalam Pembelajaran Kitab Kuning Terhadap Kepribadian Santri Di Pondok Pesantren - Khusnan, Ach (Program Studi Pendidikan Agama Islam, 2020)
Several centuries ago when humans were in the age of ignorance, Allah SWT sent His messenger by lowering the holy book to him, a book containing the guidelines for life that guide humans to the path of peace, which contains warnings and good news, in the first revelation clearly. Al-Qur'an explains with the word